Prevalence and Risk Factors associated with Extended Spectrum Beta Lactamase Producing Escherichia coli and Klebsiella pneumoniae Isolates in Hospitalized Patients in Kashan (Iran) - Sharif, Mohammad Reza (Electron Physician, 2016)
INTRODUCTION: Production of extended spectrum beta lactamase (ESBL) is an important mechanism of antimicrobial resistance in Escherichia coli (E. coli) and Klebsiella pneumoniae (K. pneumoniae) isolates. This study was performed to determine the prevalence and risk factors associated with ESBL producing strains of E. coli and K. pneumoniae. METHODS: In this cross-sectional study, 250 strains (134 E. coli and 116 K. pneumoniae) were obtained, and ESBL producing isolates were detected by the combination disk test in Shahid Beheshti Hospital in Kashan, Iran, from February 2012 to June 2013. Antimicrobial resistance was screened by the disk diffusion method and was confirmed by E-test. Furthermore, risk factors of ESBL producing E. coli and K. pneumoniae microorganisms were determined. Data were analyzed by SPSS version 16, using descriptive statistics, chi-squared, independent-samples t-test, and logistic regression analysis. RESULTS: One hundred and two (40.8%) of all strains were ESBL producers, of which 54 (52.9%) were E. coli and 48 (47.1%) were K. pneumoniae (p = 0.86). Furthermore, 40.3% of E. coli and 41.4% of K. pneumoniae isolates were ESBL producers (p = 0.86). The most antimicrobial resistance was to ampicillin, and no imipenem resistance was detected. Risk factors for ESBL producing E. coli included admission duration exceeding 7 days (p = 0.011) and antibiotic use in the last month (p < 0.001), and the associated risk factor for ESBL producing K. pneumoniae was antibiotic use during the recent month (p = 0.002). CONCLUSION: This study identified a relatively high prevalence of ESBL production among E. coli and K. pneumoniae strains. Furthermore, anti-bimicrobial use and admission duration were risk factors for ESBL producing isolates. Therefore, more comprehensive investigations are needed for the development of new strategies to control the dissemination of these microbes.